2011
DOI: 10.1159/000335804
|View full text |Cite
|
Sign up to set email alerts
|

Acute Mitochondrial Actions of Glitazones on the Liver: a Crucial Parameter for their Antidiabetic Properties

Abstract: Background/aims: Glitazones are synthetic insulin-sensitizing drugs which act as agonists of peroxisome proliferator-activated receptor gamma (PPARγ). However, TZDs action does not exclude independent PPARγ-activation effects. Remarkably, direct mitochondrial action of these agents has not been fully studied yet. Methods: Oxygen consumption rates (JO2) were measured using a Clark-type oxygen electrode in intact hepatocytes and isolated liver mitochondria. Mitochondrial reactive oxygen species (ROS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 47 publications
4
22
1
2
Order By: Relevance
“…Likewise, treatment of mice with PGZ for 12 weeks at a dose that has demonstrated to have pharmacologic effects (10 mg PGZ/g/day) [14] resulted in a significant decrease in complex I, but not complex III, activity. These results are consistent with those obtained by others with PGZ and other TZDs [7,8,15] and with those we have previously reported in ob/ob mice [12]. Although some authors found that this effect of PGZ on complex I activity was not dose-dependent [15], we found a clear relationship between the dose of PGZ and the decrease in complex activity (Figure 1A).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Likewise, treatment of mice with PGZ for 12 weeks at a dose that has demonstrated to have pharmacologic effects (10 mg PGZ/g/day) [14] resulted in a significant decrease in complex I, but not complex III, activity. These results are consistent with those obtained by others with PGZ and other TZDs [7,8,15] and with those we have previously reported in ob/ob mice [12]. Although some authors found that this effect of PGZ on complex I activity was not dose-dependent [15], we found a clear relationship between the dose of PGZ and the decrease in complex activity (Figure 1A).…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with those obtained by others with PGZ and other TZDs [7,8,15] and with those we have previously reported in ob/ob mice [12]. Although some authors found that this effect of PGZ on complex I activity was not dose-dependent [15], we found a clear relationship between the dose of PGZ and the decrease in complex activity (Figure 1A). In contrast, we found no effects of PGZ on complex II, IV, or V activity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several recent studies have proposed that PPAR γ could not be completely responsible for the insulin-sensitizing efficacy of the classical TZDs [7, 34, 35]. The identification of a novel binding site for TZDs in the mitochondrial membrane has instead suggested the presence of an alternative, PPAR γ -independent mode of action for this class of TZD drugs, which in turn signals the possibility of rationally designing insulin sensitizers that are distinct from PPAR-activating compounds.…”
Section: Pparγ-sparing Compoundsmentioning
confidence: 99%
“…More specifically, hepatic steatosis and inflammation markedly impair the ability of insulin to inhibit liver glucose production, leading to hyperglycemia and hyperinsulinemia [9, 10]. Therefore, strategies to counteract hepatic steatosis, inflammation, and increased hepatic glucose production are crucial to the prevention and treatment of chronic metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%